An Advantage of Digital Book for Business Education in Indonesia Country - Ariatmanto, Dhani (Journal of Education and Vocational Research, 2015)
The main objective of this paper is to see the opportunity of a business education about digital book that consist of media education in Indonesia country. As we know the technology of a digital book for multimedia learning are still rare use by Indonesia educational teachers, the purpose is to determine the profit business in the future for making of digital book. The research design consisted of development design. The methodology analysis that will use in this research is SWOT (Strength, Weakness, Opportunity, Threats). The result of a research is finding that the business of digital book for learning tools in Indonesia country still open wide. Recommendations have been given on the basis of findings.